إختبار العلاقة بين النمو الإقتصادي والبطالة في الجزائر خلال الفترة مابين 1980-2020 - بن رحال خديجة; بن صديق فاطمة; شرماط طاهر (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to test the relationship between economic growth and unemployment in Algeria during the period 1980/2020 by testing both the correlation and the causal sign between the logarithm of the gross domestic product as an indicator for expressing economic growth and total unemployment ecclesiastical of the total workforce and then estimating the Oken relationship. To a set of results, the most important of which is the existence of an inverse correlation between two variables, as well as the existence of a single causal relationship that moves from economic growth towards unemployment